The language of colour in the Bible embodied colour terms related to green - García Ureña, Lourdes ca. 20./21. Jh; Angelini, Anna 1979-; Murphy, Donald ca. 20./21. Jh; Salvador Gimeno, Marina; Valeriani, Emanuela (De Gruyter, 2022)
The Bible is one of the books that has aroused the most interest throughout history to the present day. However, there is one topic that has mostly been neglected and which today constitutes one of the most emblematic elements of the visual culture in which we live immersed: the language of colour. Colour is present in the biblical text from its beginning to its end, but it has hardly been studied, and we appear to have forgotten that the detailed study of the colour terms in the Bible is essential to understanding the use and symbolism that the language of colour has acquired in the literature that has forged European culture and art.
Keywords: Bibel; Farbe; Grün; kognitive Linguistik; RELIGION / Biblical Reference / Language Study